Hurricanes and climate change. Volume 3 - Collins, Jennifer M.; Walsh, Kevin (Springer, 2017)
This book provides research that shows tropical cyclones are more powerful than in the past with the most dramatic increases occurring over the North Atlantic and with the strongest hurricanes. Although such increases are correlated with warming oceans and are consistent with the thermodynamic theory of hurricane intensity, there remains doubt about the interpretation, integrity, and meaning of these results. Arising from the 5th International Summit on Hurricanes and Climate Change, this book contains new research on topics related to hurricanes and climate change. Bringing together international leading academics and researchers on various sides of the debate, the book discusses new research and expresses opinions about what is happening and what might happen in the future with regard to regional and global hurricane (tropical cyclone) activity.
Keywords: Hurricanes.; Climatic changes.; elektronické knihy; electronic books